Ideological Spillovers across the Atlantic? Evidence from Trump's Presidential Election - Joan Costa-i-Font; Martin Ljunge (Center for Economic Studies and ifo Institute (CESifo), 2022)
Ideological spillovers refer to the modification of an individual's core beliefs after learning about other people's beliefs. We study one specific international ideological spillover, namely, the effect of the unexpected election of a United States (US) president (Donald Trump on the 9th of November 2016), who openly questioned the so-called 'core liberal consensuses, on European's core political beliefs. Using a regression discontinuity design (RDD) around the election event, we show that the Trump presidential election (TPE) gave rise to a 'backlash effect'. That is, it steered core European beliefs in two specific domains, making Europeans more favourable to globalisation and international mobility (about 10% change in the overall Likert scale range of the statement that immigrants contribute to a country). Contrasting with the hypotheses of 'belief contagion', we do not find evidence that TPE steered illiberal beliefs. Furthermore, TPE improved (deteriorated) the view Europeans have of their own country (the United States).
Keywords: P16; D72; F50; Z10; 330; political shocks; belief formation; information spillovers; backlash effect; pluralistic ignorance; Trump presidential election; political beliefs; the social formation of beliefs